ORGANISATIONAL LEARNING IN SERBIA DURING THE TRANSITION: THE LEGACY OF BOŽIDAR CEROVIĆ AND HIS CONTRIBUTION TO TRANSITION RESEARCH - Aleksić Mirić, Ana; Bogićević Milikić, Biljana; Janićijević, Nebojša (Economic Annals, 2020)
In this paper we address the issue of organisational learning in Serbia during the transition, based extensively on the research work of Božidar Cerović that was published in his conference papers, academic journals, books, and edited vol-umes from the 1990s onwards, as well as in our joint research. We delineate three generations of organisational learning in the post-1989 transformation, which cor-respond to the transition periods com-prehensively analysed in Cerović’s work. We discuss each of these generations of organisational learning as characterised by the specific learning context, shaded by macro-level determinants and distinctive learning antecedents, nature, practices, and outcomes, and provide a theoretical framework using institutional organisation theory to highlight the specific issue of or-ganisational learning in Serbia during the transition of South-Eastern Europe.